In vitro cellular behaviors and toxicity assays of small-sized fluorescent silicon nanoparticles. Issue 22 (25th May 2017) - Cao, Zhaohui; Peng, Fei; Hu, Zhilin; Chu, Binbin; Zhong, Yiling; Su, Yuanyuan; He, Sudan; He, Yao
Abstract : We for the first time present a comprehensive investigation of the interaction between live cells and fluorescent small-sized (∼4 nm) SiNPs. Abstract : Extensive investigations have been carried out for evaluating the toxicology of various nanomaterials ( e.g., carbon- and metal-based nanomaterials), which offer invaluable information for assessing the feasibility of nanomaterial-based wide-ranging applications. In recent years, sufficient efforts have been made to develop fluorescent small-sized silicon nanoparticles (SiNPs) as a novel optical material simultaneously featuring strong fluorescence and ultrahigh photostability, providing high promise for a myriad of biological, biomedical and electronic applications. It is worth pointing out that, despite the non- or low-toxicity of silicon, sufficient and objective toxicology evaluation of SiNPs is urgently required at both the in vitro and in vivo levels. However, there currently exists scanty information about the intracellular behaviors of the SiNPs, particularly the underlying mechanism of entry into cells and intracellular fate. Herein, we present a report aimed at determining the uptake and intracellular transport of SiNPs of ca. 4 nm diameter. Taking advantage of the strong and stable fluorescent signals of SiNPs, we reveal that these small-sized SiNPs accumulate in the plasma membrane prior to internalization, and are further internalized predominantly by clathrin-mediated and caveolae-dependent endocytosis. After endocytosis, the SiNPs are localized in early endosomes within a short time (∼1 h), while in up to 24 h of incubation the SiNPs are mainly transported to lysosomes in a microtubule-dependent way; and interestingly, to a smaller extent are sorted to the Golgi apparatus. Moreover, we demonstrate that there are no toxic effects of SiNPs on the cell metabolic activity and integrity of the plasma membrane.